An Aberrant Case of Squamous Cell Carcinoma of Trachea in Female Patient: A Case Report - Nabha Mahajan; Suresh Phatak; Avinash Dhok; Yash Jakhotia (Journal of Clinical and Diagnostic Research, 2023)
Tracheal tumours can be either benign or malignant. Benign tumours grow slowly and may mimic the clinical presentation of chronic lung diseases, resulting in delayed diagnosis. Conversely, rapidly growing malignant tumours present early with locally advanced disease. Hereby, the authors present a case of a 54-year-old female who presented with complaints of breathlessness at rest and cough with expectoration for one year, with a background history of chronic bidi smoking for 20 years. Multidetector Computed Tomography (MDCT) showed an ill-defined soft tissue mass lesion above the carina, partially obstructing its lumen with heterogeneous post-contrast enhancement. During bronchoscopy, an endotracheal pedunculated mass was observed in the proximal one-third of the trachea, occluding the distal airway. The excised mass was confirmed as Squamous Cell Carcinoma (SCC) on histopathological examination {Haematoxylin and Eosin (H&E)}. The presence of co-morbid conditions in the patient, the site of the tumour, and the availability of treatment options are some of the factors that influence the survival rate of this rare airway tumour.